Pengaruh Minat Belajar dan Lingkungan Sekolah terhadap Hasil Belajar Siswa - A Akhmad Farhan Putra Ash-Shiddiq; Mardhiah; Nidya Nina Ichiana; Baharuddin (Alauddin Journal of Mathematics Education, 2022)
There are various factors that affect student learning outcomes, both internal and external factors. This study aims to get an overview of the influence of interest in learning and school language on mathematics learning outcomes. This research is a quantitative research with the type of ex-post facto which was conducted on class VII students of MTs Babussalam DDI Kassi. The sample was selected by simple random sampling technique. In conducting research, angles are used to measure interest in learning and the school environment as well as documentation of mathematics learning outcomes in the form of even semester scores. The data obtained were analyzed using descriptive and inferential statistics, namely simple linear regression and multiple linear regression. The results of the analysis show that students' learning interest is in the high category with an average score of 61.97, the school environment is in the medium category with an average score of 57.13, and for mathematics learning outcomes is in the medium category with an average score of 79. 26. While the inferential test shows that interest in learning and the school environment have a positive effect on learning outcomes.